Law, Environment, Africa Publication of the 5th symposium, 4th scientific conference, 2018 of the Association of Environmental Law Lecturers from African Universities in cooperation with the Climate Policy and Energy Security Programme for Sub-Saharan Africa of the Konrad-Adenauer-Stiftung and UN Environment - Law, Environment, Africa; Kameri-Mbote, Patricia; Paterson, Alexander Ross 1972-; Ruppel, Oliver C. 1969-; Orubebe, Bibobra Bello; Kam Yogo, Emmanuel Dieudonné 19XX-; Association of Environmental Law Lecturers from African Universities (Recht und Verfassung in Afrika, 2019)
Law | Environment | Africa compiles the proceedings of the 5th Symposium and the 4th Scientific Conference of the Association of Environmental Law Lecturers from African Universities (ASSELLAU) in cooperation with the Climate Policy and Energy Security Programme for Sub-Saharan Africa run by the Konrad-Adenauer-Stiftung (KAS) and the United Nations Environment Programme (UNEP). The book’s aim is to explore, review and analyse recent developments at the point where the law and the environment in Africa overlap. The collection comprises 32 chapters by legal experts from central, eastern, southern and western Africa. It is divided thematically into four parts: 1.) Climate change and energy, 2.) Natural resource governance, 3.) Water governance, management and use; and 4.) The role of the law in regulating social and environmental impacts associated with human activity. These subjects are discussed in the context of national, regional and international law frameworks, which are central to Africa’s quest to attain its desired and sustainable development trajectory within the confines of the continent’s valuable yet fragile ecological infrastructure.